The Effectiveness of Entomopathogenic Nematode Steinernema spp. on Mortality of Lepidiota stigma F. (Coleoptera: Scarabaeidae) - Toto - Sunarto; Aep Wawan Irwan (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Integrated Pest Management (IPM) is an alternative way to reduce use of synthetic pesticides. One of them is using the natural enemy of insect pests, such as predatory insects, parasitoid, and entomopathogenic nematodes. So far the control of Lepidiota stigma F. in sweet potatoes carried out with synthetic insecticides that has negative impact to the environment. Another alternative of L. stigma control with entomopathogenic nematodes (Steinernema spp.). This study aimed to obtain Steinernema spp. concentration that effective against mortality of L. stigma larvae. This experiment was conducted at Plant Nematology Laboratory, Faculty of Agriculture, Universitas Padjadjaran from Februari - August 2019. The research used was experiment method with Completely Randomized Design consisted of six treatments and five replications. The treatment were Steinernema spp. concentration of 0, 50, 100, 150, 200 IJ ml-1 of water, and Karbofuran dose of 15 kg ha-1 (0.002 g / 12.56 cm2). The results showed that Sterinernema spp. has an effect on mortality of Lepidiota stigma larvae at 24 HAA (Hours After Application) and 48 HAA. Steinernema spp. at concentration of 150 IJ ml-1 capable effectively causing the mortality of Lepidiota stigma larvae of 68% at 48 HAA.